Menyingkap Arena Kuasa Simbolik Islam Ideologis (Studi Lapangan di Yogyakarta) - Zulkarnain, Iskandar (Universitas Bangka Belitung, 2009)
The researcher discusses the symbolical power field of Hizbut Tahrir Indonesia (HTI) and Majelis Mujahidin Indonesia (MMI) which fight the strategic arena as the political tools to achieve the substantive power after the order regime. HTI and MMI as ideological Islam organizations which struggle Islamic Syariah formalization in state and nation order can be analyzed using Pierre Bordieu conceptual framework. It consists of three key concepts as follow: habitus, champ and symbolic power. Those key concepts are formulated in political dakwah and jihad which invite personnelâs or among members to change an old paradigm to a new paradigm (fully syariah) to create a uniformity and habitus reproductions.Field of struggles are directed to dominate political fields which institutional based, community based, and governmental institutions through an economic capital hegemony, a culture, a social and symbolic powers. The economic capital can be means of production possession, materials, and money changes as inherited investment in a long period. Culture capitals are accumulated into intellectual hegemony, discourses, and argumentations to get social positions. The culture capitals are directed to social networks (cooperationâs) ownership and authorities in relation to an other stakeholder or power holders. Symbolic capitals is the accumulation of economic, culture and social capitals which deal with a prestige, status, authority and legitimacy from other stakeholders. A symbolic capital hegemony is the centre of field of struggles domination and requirements to get symbolic powers.